Design of a synthetic indigo dye plant - Belardo, Luisito A. (College of Engineering, 1961)
This report is an extensive study of the feasibility of establishing an indigo eye plant in the Philippines. It is the summation of a semester's work of research, computations, design and compilation. An exhaustive literature and market survey led us to choose a method of manufacture which is based mainly on Heumann's phenylglycine synthesis. This involves the formation of phenylglycine from the condensation of aniline and chloroacetic acid, then fusing it with caustic soda and potash and finally air-oxidizing it to produce the final product--indigo. This proposed plant will be erected in Novaliches. It requires an initial investment of P3,364,159.00 with a fixed capital investment of P1,947,601.00. The percent return on investment before taxes is 25 percent and a profit after taxes of P829,735.75. The pay-out time after taxes is 2.89 years. This profitability estimate is based on the assumption that the whole bulk of the product could be disposed of promptly.